Effect of combination of rapamycin and cisplatin on human cervical carcinoma Hela cells - Han, Lu; Wu, Jie-Ling; Yang, Li-Xiao (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: To evaluate the effect of combined use of rapamycin and cisplatin against Hela cells in vitro . Material and methods : The inhibitory effects of rapamycin and cisplatin, used alone or combination, on the proliferation of Hela cell were measured with MTT assay and median-effect plot analysis. Results : Combined use of rapamycin and cisplatin significantly improved the chemotherapeutic effect against Hela cells. The inhibitory rates were dose-dependent. Rapamycin and cisplatin showed synergistic effects in the chemotherapy of Hela cells (q > 1.15, King’s formula). Conclusions : Combined use of rapamycin and cisplatin significantly improves the chemotherapeutic effect against Hela cells.